2003
DOI: 10.1034/j.1600-0420.2003.00063.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of vasomotion in porcine retinal arterioles

Abstract: ABSTRACT.Purpose: To characterize vasomotion in porcine retinal arterioles in vitro using isobaric (pressure myograph) and isometric (wire myograph) methods. Methods: Pressure myograph: 208 small porcine retinal arterioles (outer diameter 68 AE 4 mm) were studied under isobaric conditions in a double-barrelled pipette system. Diameter changes of the arterioles were registered by video recordings. Wire myograph: 60 large porcine retinal arterioles (inner diameter 147 AE 1.6 mm) were studied under isometric cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 25 publications
(33 reference statements)
1
41
0
Order By: Relevance
“…The vein was suspended in physiological saline solution (PSS) containing calcium and contractile studies undertaken as previously described (Hessellund et al, 2003). The dissected vessels were attached onto the force transducer of a myograph (Danish Myo Technology) and allowed to equilibrate for 60 min in oxygenated PSS (5% CO 2 in air).…”
Section: Organ Bath Studiesmentioning
confidence: 99%
“…The vein was suspended in physiological saline solution (PSS) containing calcium and contractile studies undertaken as previously described (Hessellund et al, 2003). The dissected vessels were attached onto the force transducer of a myograph (Danish Myo Technology) and allowed to equilibrate for 60 min in oxygenated PSS (5% CO 2 in air).…”
Section: Organ Bath Studiesmentioning
confidence: 99%
“…These oscillations can be interpreted as vasomotion. There are several other studies in isolated porcine (Hoste et al 1989;Nyborg et al 1990;Yu et al 1994;Hessellund et al 2003;Jeppesen et al 2003) or bovine (Delaey & Van de Voorde 2000) retinal arteries studied in a myograph that also suggest basal oscillations in vascular tone. We believe that in this model vasomotion was enhanced because of hypotension, hypoxia and the accumulation of endothelial vasoacting substances.…”
Section: Discussionmentioning
confidence: 99%
“…Vasomotion refers to periodic oscillations in vascular tone that ensure the intermittent supply of blood to adjacent microvascular units , resulting from the action of pacemaker cells in the vascular walls and ⁄ or from the vascular endothelium (Hessellund et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…One wire was attached to the micrometer and the other to a force displacement transducer for isometric force measurements (Hessellund et al 2003). The vessel was allowed to equilibrate for approximately 30 mins in heated (37 ) PSS before it was normalized to a standardized level of passive tension.…”
Section: Mounting and Normalizationmentioning
confidence: 99%
“…The physiological role of this phenomenon is to allow fine control of the capillary blood flow and to facilitate the exchange of metabolites between capillaries and tissue (Papenfuss & Gross 1985;Tsai & Intaglietta 1993). Vasomotion has been observed in almost all vascular beds hitherto studied (Johansson & Bohr 1966;Osol & Halpern 1988;Gustafsson 1993), including the retina (Riva et al 1990;Braun et al 1992;Hessellund et al 2003), and evidence suggests that disturbances in vasomotion are involved in the pathogenesis of vascular complications in arterial hypertension (Mulvany 1988) and diabetes mellitus (Stansberry et al 1996;Renaudin et al 1999). It has been suggested that disturbances in retinal vasomotion may be involved in the pathophysiology of diabetic maculopathy (Bek 1999).…”
Section: Introductionmentioning
confidence: 99%